Understanding the Reciprocal Interplay Between Antibiotics and Host Immune System: How Can We Improve the Anti-Mycobacterial Activity of Current Drugs to Better Control Tuberculosis? - Park, Hyun-Eui; Lee, Wonsik; Shin, Min-Kyoung; Shin, Sung Jae (Frontiers in Immunology, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb) infection, remains a global health threat despite recent advances and insights into host-pathogen interactions and the identification of diverse pathways that may be novel therapeutic targets for TB treatment. In addition, the emergence and spread of multidrug-resistant Mtb strains led to a low success rate of TB treatments. Thus, novel strategies involving the host immune system that boost the effectiveness of existing antibiotics have been recently suggested to better control TB. However, the lack of comprehensive understanding of the immunomodulatory effects of anti-TB drugs, including first-line drugs and newly introduced antibiotics, on bystander and effector immune cells curtailed the development of effective therapeutic strategies to combat Mtb infection. In this review, we focus on the influence of host immune-mediated stresses, such as lysosomal activation, metabolic changes, oxidative stress, mitochondrial damage, and immune mediators, on the activities of anti-TB drugs. In addition, we discuss how anti-TB drugs facilitate the generation of Mtb populations that are resistant to host immune response or disrupt host immunity. Thus, further understanding the interplay between anti-TB drugs and host immune responses may enhance effective host antimicrobial activities and prevent Mtb tolerance to antibiotic and immune attacks. Finally, this review highlights novel adjunctive therapeutic approaches against Mtb infection for better disease outcomes, shorter treatment duration, and improved treatment efficacy based on reciprocal interactions between current TB antibiotics and host immune cells.